Konstribusi Kepala Madrasah dalam Menumbuhkan Perilaku Organisasi di MAN 1 Kota Kediri - Rahadian Fatawi (JoIEM (Journal of Islamic Education Management), 2023)
The madrasa head is a professional official who has a strategic role in educational institutions. This study aims to: explore some strategies and efforts of madrasa heads in cultivating organizational behavior in MAN 1, Kediri. This study used a qualitative approach, with a case study design at MAN 1 Kediri City. The collection of research data was carried out through non-participant observation. Data analysis was carried out in three stages, namely data collection, data reduction, and data presentation. This research produced two findings, the first is organizational behavior which is individual behavior in an educational organization that involves many components including teachers, staff, and employees. Madrasas play an important role in overcoming these different behaviors. the head of the madrasa at MAN 1 Kota Kediri took the method by giving assignments according to their educational background, skills, and abilities. The existence of differences in the organization can be organized and does not cause conflict within the organization. Secondly, by organizing differences in the organization, teachers can work safely, comfortably, and under control. that way the work of teachers and employees can run effectively and efficiently, and the organization can improve according to the expected goals